The transitioning from trials to extended follow-up studies. (December 2014) - Drye, Lea T; Casper, Anne S; Sternberg, Alice L; Holbrook, Janet T; Jenkins, Gabrielle; Meinert, Curtis L
Background: Investigators may elect to extend follow-up of participants enrolled in a randomized clinical trial after the trial comes to its planned end. The additional follow-up may be initiated to learn about longer term effects of treatments, including adverse events, costs related to treatment, or for reasons unrelated to treatment such as to observe the natural course of the disease using the established cohort from the trial. Purpose: We examine transitioning from trials to extended follow-up studies when the goal of additional follow-up is to observe longer term treatment effects. Methods: We conducted a literature search in selected journals from 2000 to 2012 to identify trials that extended follow-up for the purpose of studying longer term treatment effects and extracted information on the operational and logistical issues in the transition. We also draw experience from three trials coordinated by the Johns Hopkins Coordinating Centers that made transitions to extended follow-up: the Alzheimer's Disease Anti-inflammatory Prevention Trial, Multicenter Uveitis Steroid Treatment trial, and Childhood Asthma Management Program. Results: Transitions are not uncommon in multicenter clinical trials, even in trials that continued to the planned end of the trial. Transitioning usually necessitates new participant consents. If study infrastructure is not maintained during the transition, participants will be lost and re-establishing the staff and facilities will be costly. Merging data from the trial and follow-up study can be complicated by changes in data collection measures and schedules. Limitations: Our discussion and recommendations are limited to issues that we have experienced in transitions from trials to follow-up studies. Discussion: We discuss issues such as maintaining funding, institutional review board and consent requirements, contacting participants, and combining data from the trial and follow-up phases. We conclude with a list of recommendations to facilitate transitions from a trial to an extended follow-up study.